2010
DOI: 10.1007/s00436-010-2092-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of cox1 and nad1 genes in Echinococcus granulosus G3 genotype in camels (Camelus dromedarius) from central Iran

Abstract: Nineteen hydatid cyst isolates collected from camels in central Iran were subjected to sequences analysis of mitochondrial cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1) genes. A consensus sequence obtained containing 366 nucleotides for cox1 and 471 nucleotides for nad1 genes. Overall, the camel isolates indicated five different sequences in cox1 and nine in nad1 genes. The sequences analysis indicated that 26.3%, 42.1%, and 31.6% of isolates belonging to G1, G3, and G6 genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 39 publications
6
43
0
Order By: Relevance
“…Sharbatkhori and others 30 found that all 34 sheep isolates investigated from Tehran Province indicated the G1 genotype, in concordance with the findings of the highest prevalence of G1 genotype in humans in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Sharbatkhori and others 30 found that all 34 sheep isolates investigated from Tehran Province indicated the G1 genotype, in concordance with the findings of the highest prevalence of G1 genotype in humans in this study.…”
Section: Discussionsupporting
confidence: 92%
“…[48][49][50][51][52][53][54][55] For the first time in Iran, Sharbatkhori and others 30 reported the occurrence of the G3 genotype in camels from the Isfahan Province (central Iran). This was a global first for the identification of the G3 genotype in this host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of partial mitochondrial ND1 sequence data revealed a C/T change at position 195 in human, sheep and cattle isolates (HQ717151) that has been reported in many isolates from various parts of the world (including HM853645, DQ856470 and AF408688, among others) and from Turkey (13,(45)(46)(47). The co-occurrence of the 195 C/T and 288 T/C changes (HQ717152) has been previously noted [FJ796212 (22)].…”
Section: Discussionmentioning
confidence: 76%
“…These questions have subsequently been resolved with the advent of reliable, robust and reproducible molecular tools which have not only supported the early taxonomy, but also demonstrated the distinctness of transmission cycles and the potential for interaction, particularly with respect to zoonotic transmission [95,103,106]. Importantly, these molecular epidemiological studies have given confidence to the morphological characters used for species discrimination which now offer a simple, cost effective means of parasite identification in endemic foci where the application of molecular tools may not be practical or cost-effective [107,108].…”
Section: Echinococcus Giardia and Cryptosporidiummentioning
confidence: 99%